2007
DOI: 10.1245/s10434-007-9571-9
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Oxaliplatin During Open Versus Laparoscopically Assisted Heated Intraoperative Intraperitoneal Chemotherapy (HIPEC): An Experimental Study

Abstract: This study confirms the technical feasibility and reliability of the laparoscopic approach for HIPEC, and it extends knowledge concerning peritoneal drug absorption. Oxaliplatin absorption is far higher with laparoscopy in terms of time course in peritoneal perfusion. Clinical application in selected patients may be expected after further experimental investigation designed to define the adequate drug dosage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 16 publications
1
47
0
Order By: Relevance
“…In a pig model, laparoscopic hyperthermic intraperitoneal chemotherapy (HIPEC), associated with an increased intra-abdominal pressure, resulted in higher drug absorption from the abdominal cavity to the systemic compartment when compared with the open abdomen, coliseum technique [55]. The practical use of highly increased intra-abdominal pressure is restricted by its adverse effect on the respiratory and hemodynamic systems.…”
Section: Intra-abdominal Pressurementioning
confidence: 99%
“…In a pig model, laparoscopic hyperthermic intraperitoneal chemotherapy (HIPEC), associated with an increased intra-abdominal pressure, resulted in higher drug absorption from the abdominal cavity to the systemic compartment when compared with the open abdomen, coliseum technique [55]. The practical use of highly increased intra-abdominal pressure is restricted by its adverse effect on the respiratory and hemodynamic systems.…”
Section: Intra-abdominal Pressurementioning
confidence: 99%
“…In the present medical environment where there is a constant quest for minimally invasive procedures, two recent cohorts of patients treated with laparoscopic CRS and HIPEC versus laparotomy presented no significant differences in postoperative morbidity and mortality between the two approaches, identifying laparoscopic HIPEC as a safe and efficient alternative (67,75,76).…”
Section: Laparoscopic Hipecmentioning
confidence: 93%
“…However, in addition to the direct drug delivery system in open laparotomy, there have been advances in the minimally invasive surgical techniques, allowing for the introduction of the laparoscopic HIPEC therapy. In terms of efficacy, an animal study demonstrated increased drug perfusion with the laparoscopic technique (66,67).…”
Section: Direct Peritoneal Chemotherapymentioning
confidence: 99%
“…Recently, intraperitoneal chemohyperthermia has attracted further attention and been widely used throughout the world, achieving satisfactory therapeutic outcomes. [4][5][6] The National Cancer Research Institute in Italy has carried out stage II testing of intraperitoneal chemohyperthermia (cisplatin + mitomycin C) in 27 cases of recurrent ovarian cancer, and the two-year survival rate was 55%, with a median time to local tumor progression of 21.8 months. Of note, a stage III study of 415 patients with end-stage ovarian cancer showed that the median survival time in patients treated with combined chemotherapy via the venous and abdominal cavity routes was 65.6 months, while that of patients who received only intravenous chemotherapy was 49.7 months.…”
Section: Introductionmentioning
confidence: 99%